Hubungan Minat Belajar dengan Hasil Belajar Kognitif Pendidikan Pancasila Siswa Kelas V SDN 5 Banyumanis - Adelia, Vindy Audina; Rondli, Wawan Shokib; Santoso, Denni Agung (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
The low learning interest among students at SDN 5 Banyumanis served as the background of this study, characterized by a monotonous instructional process limited to textbooks and dominated by rote memorization methods. This condition has adversely affected students’ academic achievement, particularly in the Pancasila Education subject, where outcomes fall below the Minimum Achievement Criteria (Kriteria Ketercapaian Tujuan Pembelajaran, KKTP). The objective of this study is to analyze the relationship and influence of learning interest on the cognitive learning outcomes of fifth-grade students. A quantitative approach with a correlational design and simple linear regression analysis was used. The research involved 25 fifth-grade students selected through total sampling. Data were collected using questionnaires, observation, interviews, and documentation, and analyzed using normality tests, linearity tests, Pearson Product Moment correlation, and simple linear regression. The results indicate a significant positive correlation between learning interest and cognitive learning outcomes, with a correlation coefficient of 0.777 and a significance value of 0.000 (p < 0.05). The resulting regression equation is Ŷ = 8.881 + 2.252X, with a determination value (R²) of 0.603, indicating that learning interest contributes 60.3% to the variation in students’ cognitive learning outcomes. The study concludes that learning interest has a significant and substantial impact on cognitive achievement. The findings suggest that teachers should adopt more varied and engaging instructional strategies, such as multimedia-based Problem-Based Learning, to foster a participatory and contextual learning environment. This study also opens avenues for further exploration of external factors influencing student learning outcomes.